Differential gene expression during berry ripening in Vitis vinifera (cv Chardonnay) : isolation of specific sequences through subtractive cloning - Olivier, Abraham Jacobus (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2002.